2018
DOI: 10.1097/igc.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is an Important Prognostic Factor in Patients With Cervical Cancer Undergoing Concurrent Chemoradiotherapy

Abstract: Sarcopenia (≥15.0% loss of IM from baseline) was revealed to be an important prognostic factor in patients with CC undergoing CCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…Evaluating muscle at a single specific time point may not help in predicting survival and could not evaluate muscle loss . These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluating muscle at a single specific time point may not help in predicting survival and could not evaluate muscle loss . These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes …”
Section: Discussionmentioning
confidence: 99%
“…49,62 These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes. [40][41][42][43][44][45][46][47][48][49] Body mass index is an imprecise measure of body composition, and monitoring BMI changes may be insufficient to promptly identify occult body composition changes. 18,19 We found that changes in SMI and TATI were weakly correlated with the change in BMI, and changes in SMD and SMG showed no correlation with the BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiposity was also an independent prognostic factor of outcomes according to three recent large studies (19)(20)(21). Longitudinal studies of body composition change during treatment (15)(16)(17)(18) may provide a more comprehensive picture of how body composition is associated with outcomes. However, there is a paucity of data on the potential effect of skeletal muscle and adipose tissue change during CCRT on the outcomes of patients with LACC.…”
Section: Introductionmentioning
confidence: 97%
“…During the course of CCRT, gastrointestinal toxicities could potentially contribute to weight loss, nutrient malabsorption, and even malnutrition in these patients (4,5); therefore, the body composition including skeletal muscle and adipose tissue might change during CCRT, and this change could play a role in cancer outcomes (6,7). Emerging evidence suggests that sarcopenia is associated with a poor prognosis and increased treatment-related toxicities in patients with metastatic and non-metastatic cancers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Adiposity was also an independent prognostic factor of outcomes according to three recent large studies (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%